2020
DOI: 10.3390/nu12103173
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to a Mediterranean Diet and Thyroid Function in Obesity: A Cross-Sectional Apulian Survey

Abstract: Much research suggests that Mediterranean eating habits and lifestyle contribute to counteract the risk of chronic diseases while promoting longevity, but little information is available on the effects of the Mediterranean diet (Med-Diet) on thyroid function, particularly among overweight/obese subjects. Nevertheless, consistent data reported a slight increase in serum levels of the thyroid-stimulating hormone (TSH) and a higher rate of conversion of thyroxine (T4) to triiodothyronine (T3) in obesity. This cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
35
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 33 publications
0
35
2
Order By: Relevance
“…Not relevant to the topic examined studies, studies including population <18 years old, studies in which validated tool for assessment of MD were not used and in which the level of adherence was not clearly described were excluded. Overall, 58 studies were characterized as acceptable for the systematic review [ 39 , 40 , 43 , 44 , 45 , 46 , 47 , 49 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 ,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Not relevant to the topic examined studies, studies including population <18 years old, studies in which validated tool for assessment of MD were not used and in which the level of adherence was not clearly described were excluded. Overall, 58 studies were characterized as acceptable for the systematic review [ 39 , 40 , 43 , 44 , 45 , 46 , 47 , 49 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 ,…”
Section: Resultsmentioning
confidence: 99%
“…The quality of the 58 included studies was examined according to the NOS [ 50 ]. Five studies were characterized as unsatisfactory due to their ratings (2–4 stars) [ 43 , 67 , 75 , 80 , 107 ], whereas for 17 studies the quality was only satisfactory (5–6 stars) [ 39 , 49 , 61 , 63 , 71 , 86 , 92 , 93 , 94 , 96 , 97 , 100 , 104 , 105 ]. The majority of the included studies ( n = 28) [ 40 , 44 , 45 , 47 , 58 , 59 , 60 , 62 , 65 , 68 , 69 , 70 , 72 , 74 , 76 , 77 , 79 , 81 , 82 , 83 , 84 , 85 , 87 , 88 , 95 , 101 , 103 , 106 ] were good quality studies (7–8 stars), and eight studies were at the top of quality studies scoring 9 stars [ 46 …”
Section: Resultsmentioning
confidence: 99%
“…The mechanism by which olive derivatives and olive oil affect the TSH and thyroid hormone levels is still unclear [ 110 ]. To our knowledge, only one study in humans has shown the effect of olive oil consumption on thyroid hormone levels [ 120 ]. Zupo et al, showed that people consuming olive oil have lower levels of fT3 and fT4 [ 120 ].…”
Section: Environmental Factors That Influence Tsh and Thyroid Hormone Levelsmentioning
confidence: 99%
“…To our knowledge, only one study in humans has shown the effect of olive oil consumption on thyroid hormone levels [ 120 ]. Zupo et al, showed that people consuming olive oil have lower levels of fT3 and fT4 [ 120 ]. They also observed that the Mediterranean diet, rich in olive oil, slightly inhibits the production of fT3 and fT4 without significantly affecting thyroid function [ 120 ].…”
Section: Environmental Factors That Influence Tsh and Thyroid Hormone Levelsmentioning
confidence: 99%
“…Nevertheless, consistent data reported a slight increase in serum levels of the thyroid-stimulating hormone (TSH) and a higher rate of conversion of thyroxine (T 4 ) to triiodothyronine (T 3 ) in obesity. In cross-sectional study authors [5] investigated the relationship between adherence to the Med-Diet and circulating thyroid hormones in a cohort of overweight/obese subjects Southern Italy. 324 consecutive outpatient subjects (228 women and 96 men, age range 14-72 years) taking no drug therapy and showing normal levels of thyroid hormones, but complicated by overweight and obesity were involved in the study.…”
mentioning
confidence: 99%